Komputerisasi Sistem Verifikasi Nilai Raport Secara Multiuser pada Madrasah Tsanawiyah Negeri Tanon Sragen - Siti Aminatun, Bebas Widada, Sri Hariyati Fitriasih (STMIK Sinar Nusantara, 2012)
Based on the research results about the processing of report cards at the State Islamic Junior High School (MTsN) obtained Tanon data processing Madrasah report cards in the manual so it's pretty much weakness. research goal is to create an application that can be considered for MTsN Tanon in computerized processing in multi-user report cards. The methods used were observation and interviews. Research results are input process data relating to the transcripts, grades processing, verifying the value of the value of report cards. This application also comes with an additional menu in the form of backup, reindex, and restore the system to a continuation of the long-term application. Keyword: grades, report cards, applications, multi-user, MTsN